Comparison of Creatine Kinase Myocardial Band (CK-MB) and High Sensitive Troponin I (hsTnI) Values Between Athletes and Sedentary People - Çakaroğlu, Deniz; Kaya, Mustafa Oğuzhan (Progress in Nutrition, 2020)
Study Objectives: This study was conducted to examine and compare CK-MB and hsTnI values between people who exercise regularly and actively and those who do not, considering that men have a higher muscle mass than women, but also the higher amount of estrogen secreted in women. Methods: The test group was composed of 18 men, 17 women, a total of 35 (23.28±4.09 years) persons who engaged in active sports with no problems in terms of blood measurement. The control group was formed from a total of 34 (24.50±5.60 years) persons, including 17 men and 17 women with a sedentary lifestyle that do not engage any sport. Statistical analyses were evaluated in the SPSS program and the Independent Samples t Test was used to determine the difference between the groups. Results: The CK-MB values of active athletes were found to be less than 5 U/L (1.95±1.04), which is the mean value, and higher values than the control group. hsTnI values have a significant difference between the test group and the control group and this difference was found to below the middle level. The mean CK-MB and hsTnI values of men participants were found to be statistically significant, with more than the mean value of women participants. The men test group CK-MB values were found to be higher than the control group and there was a significant difference (p<0.05). There was no statistically significant difference in hsTnI values between men’s test and control groups. Conclusion: As a result of CK-MB and hsTnI measurements of the women test and control groups, it was observed that there was no significant difference between them. Herewith, it has been revealed that there are differences in CK-MB and hsTnI values among those who do active sports compared to those who do not, but also among women and men.